(untitled) - Welsh, Kate Shoup (Hoboken, N.J., 2007)
Part I shows every Windows Vista tool and how to use it. Part II provides step-by-step instructions for more than 140 key tasks and techniques. Both are arranged alphabetically and illustrated in full color. It's the ultimate Visual resource.
Keywords: Operating systems (Computers),Hệ điều hành (Máy tính)